The Multidimensional Livelihood Vulnerability Index – an instrument to measure livelihood vulnerability to change in the Hindu Kush Himalayas. (23rd February 2017) - Gerlitz, Jean-Yves; Macchi, Mirjam; Brooks, Nick; Pandey, Rajiv; Banerjee, Soumyadeep; Jha, Shashidhar Kumar
Abstract : In recent years the population of the Hindu Kush Himalayas (HKH) has been confronted with rapid social, economic, demographic, and political changes. In addition, the region is particularly vulnerable to climate change. However, there is a scarcity of cohesive information on the state of the environment and on the socio-economic situation of the approximately 210 million people who reside in the HKH. Specifically, data on livelihood vulnerability are lacking. As part of the Himalaya Climate Change Adaptation Programme, the International Centre for Integrated Mountain Development, in consultation with regional and international partners, has developed the Multidimensional Livelihood Vulnerability Index (MLVI), a measure to explore and describe livelihood vulnerability to climatic, environmental, and socio-economic change in the HKH region. This paper documents how the MLVI was developed and demonstrates the utility of this approach by using primary household survey data of 16 selected districts of three sub-basins in the HKH region. The analysis gives important clues about differences in the intensity and composition of multidimensional livelihood vulnerability across these locations that should be useful to decision makers to identify areas of intervention and guide their measures to reduce vulnerability.